Hydro-morphological reconstruction of the Blanco River in the eruptive event 2008: Variables that influenced the change of the channel course in Chaitén, Chile - Rojas-Castillo, Ivan Javier; Mazzorana, Bruno; Iribarren-Anacona, Pablo; Fonseca-Gallardo, Duilio; Berkhoff, Jorge Andres; Durán, Gonzalo; Iroume, Andrés (Journal of South American Earth Sciences, 2025)
Chaitén, a city in Chilean Patagonia, was hit by lahar flows from the Blanco River in May 2008 following a massive volcanic eruption. This cascade process resulted in the avulsion of the active channel of the Blanco River, dividing the city into two sectors, destroying built environments, and causing displacement of the local population. Hydrodynamic studies in the area have generally been based on post-event environmental conditions. However, an exhaustive reconstruction of the hydrodynamic behavior and associated river dynamics has not been performed. More fundamentally, no clear methodological approach has been proposed to accomplish this task. The present study addresses these challenges by applying non-conventional methods to reconstruct the initial and boundary conditions of the event and to trace the intervening factors that decisively influenced the hydrogeomorphic adjustments in the distal river segments. The reconstruction of the initial and boundary conditions of the event was performed by collecting primary and secondary information (using mixed methods and applying information triangulation). A conceptual model of the hydro-geomorphic evolution of the Blanco River in May 2008 was generated, elucidating the role of rainfall and morphodynamical responses and effects in the Blanco River and emphasizing the hydraulic behavior of the Blanco River bridge. Through the detailed reconstruction of the hydro-geomorphic processes, it could be corroborated that the channel responses were not exclusively due to the volcanic eruption but instead to a combination of massive sediment injections into the fluvial system, the intensity and spatiality of the precipitation pulses (associated with the presence of a frontal system and an atmospheric river), the mobilization of inorganic and organic sediments and the interaction of the flow with the Blanco River bridge.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Atmospheric river-front; Avulsion; Chilean Patagonia; Hydro-geomorphology; Non-conventional information; Reconstruction process; Risk management